Evaluation of the respiratory symptoms and pulmonary function tests capacities in Yazd tile workers - GH Halvani; M Ebrahimzade; H Hobobati; R Jafari nodoushan (طب کار)
Abstract Background: Tile workers are exposed to a lot of dusts and are susceptible to various pulmonary complications. This study was designed to evaluate the respiratory symptoms and lung capacities of tile workers. Methods: This was a retrospective, cross sectional study on 350 workers in different factory workshops. We assessed respiratory complaints and pulmonary function tests. Data were analyzed by SPSS using T-Test and ANOVA. Results: Among respiratory complaint, dyspnea was the most frequent(22.9%), and cough(13.1%) and sputum production(5.4%) were in the 2nd and 3rd orders. There was a significant relationship between dyspnea and reduction in spirometric indices(P< 0.05),and there was a significant relationship between respiratory complaint and job title, frequency of respiratory symptoms were higher among foundry workers. Conclusion: It is clear that occupational exposures affect pulmonary function, performing pulmonary function tests may show lung term effect of these exposures.